Interception of a free-rotating satellite: an autonomous rendezvous scenario - Karol Seweryn; Marek Banaszkiewicz (Journal of Telecommunications and Information Technology, 2023)
The spacecraft’s lifetime is often limited by reliability and redundancy of its components. Furthermore, serious restrictions on duration of spacecraft operations are posed by finite amount of fuel or cooling agent. It is also clear that once a satellite is launched, it is extremely difficult to replace/modify its hardware on the orbit. Future spacecraft missions, especially huge planetary orbiters, will require servicing support from autonomous unmanned satellites. In this paper we introduce and analyze a new scenario for interception of a free rotating satellite ion a Keplerian orbit. The scenario is divided into several stages to be executed by the servicing satellite: attitude determination of the target object; own motion planning; determination of the optimal target position and orientation before docking; controlled approach, i.e., decreasing of a range between satellites; orbiting of the servicing satellite around the target satellite; docking, i.e., radial degreasing of the intersatellite range till the satellites contact, while keeping constant the relative orienta- tion between them. The control algorithm for the servicing satellite motion during its maneuvers is described. Finally, a few examples of satellite motion simulations according to the proposed scenario are presented.